Evaluation of soil-test methods for predicting iron availability to sorghum (Sorghum bicolor) in alluvial soils of Punjab, India - SANDHU, KANWALJEET; BANSAL, R L (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during the rainy season (kharif) 1998 to explore soil-test methods for iron estimation in sorghum [Sorghum bicoior (L.) Moench] on alluvial soils. Seven chemical extractants were tested for their relative performance to predict the response of sorghum to Fe application in coarse to medium-textured alkaline alluvial soils. Three out of 7 extractants were found promising for the estimation of criticallevel of available Fe in these soils. The highest coefficients of correlation between available Fe and relative grain yield was with 1 M NH4HCO, + 0.005 M DTPA (r=0.618**), followed by IN NH40Ac + 0.1 % hydroquinone (r=0.582**) and 0.005 M DTPA (r=0.501 *). The critical deficiency level of soil available Fe with 1M NH4HC03 +0.005 M DTPA(pH 7.6),1 NNHpAc+ 0.1 % hydroquinone and 0,005 M DTPA which separated responsive soils front non-responsive ones was 15.0,22.9 and 5.8 mg/kg soil respectively.